NUNS’ DAILY LIFE AND RELIGIOUS IN THE MODERN SPAIN ACROSS HIS ACCOUNTINGS. THE CONVENT NATIVE OF CORDOBA OF HOLY ANA AT THE END OF THE FORMER REGIME. - Gómez Navarro, Soledad (Revista de Historia Social y de las Mentalidades, 2011)
In the current effervescence of the studies on the feminine monasticism in the Modern Spain, this article approaches how his intrahistoria can be known, collaborating this way to filling a certain still existing emptiness in this plot, from the analysis of the documentation deprived of a monastic economy and of the compared history, with the objective double of presenting the possibilities and weaknesses of the above mentioned source and the panorama that his contest offers for different facets of the collective life cenobítica. Real, so, scientific contribution to the knowledge of the modernist historiography in this area for the nature of the analyzed and, documentation especially, the originality of his approach.;